ANALISIS FRAUD SISTEM PEMBAYARAN CASH ON DELIVERY PADA PERUSAHAAN HONESTBEE - Arnold Subhan (Jurnal Ilmiah Mahasiswa FEB, 2017)
This study aims to determine whether there is Fraud and moral hazard performed by employees on the COD payment system. The analysis is done by interviewing the company’s managers, processing the interview result, and concluding whether or not gaps for fraud and moral hazard exist. The results show that fraud and moral hazard are not performed by the employees. However, gaps for the inappropriate conducts are still found. The researcher has provided ways to close the gaps to close the gaps in order to improve the company’s system.Keywords: fraud, system, COD